Socialist alternatives : an international journal of debate and analysis = Alternativi - McGill University. Centre for Developing-Area Studies (Montreal Centre for Developing-Area Studies, 1991)
Promotes dialogue among activists and social thinkers in different part of the world.
Published also in Russian
Keywords: Socialism and related systems; SOCIALISM; Socialists; PERIODICALS